INFLUENCIA DE LA ADICIÓN DE NANO Y MICROSÍLICE EN LA ESTABILIDAD TÉRMICA DE UNA RESINA EPOXI. APLICACIONES DEL ANOVA FUNCIONAL - Tarrío, Javier; Naya, Salvador (Revista Colombiana de Estadística, 2011)
The main purpose of this work has been the use of a new technique that combines the functional analysis and design of experiments: a one way functional ANOVA. Using this tool is intended to measure the influence of the addition of a mixture of nano and micro particles of silica fume, by-product of silicon industry, on the thermal degradation of epoxy resin. To achieve this, it has been performed a design of experiments with a treatment factor (amount of fumed silica) at three different levels. The data were obtained using thermogravimetric analysis (TG), resulting in five curves or degradation pathways by level. The functional ANOVA uses all information of each curve or functional data.The use of functional ANOVA from TG data has resulted in the amount of silica fume significantly affect the thermal stability of the compound and the epoxy resin involved in each sample. These facts may be indicative of the interaction between the organic and the inorganic phase.